Anaesthetic management of twin pregnancy with complete heart block: A continuing dilemma - Anju Rani; Alka Dahiya; Sudha Puhal; Vasudha Govil; Ritu Baloda; Sudhir Bisherwal (Journal of Preventive and Complementary Medicine)
Background: Complete heart block (CHB) during pregnancy poses significant anesthetic challenges, particularly when associated with bradycardia, and in the absence of established perioperative management guidelines. Anesthesiologists must navigate the delicate balance of maintaining hemodynamic stability while avoiding medications that could worsen bradycardia, requiring a personalized approach.Case Presentation: We present the case of a 26-year-old woman, G2P2L1, with a dichorionic diamniotic (DCDA) twin pregnancy. One fetus had intrauterine demise (IUD) at term, and the surviving twin was in a malpresentation. The patient had a history of congenital CHB with a baseline heart rate of 42–45 beats per minute but was asymptomatic and had never required a pacemaker. An emergency lower segment cesarean section (LSCS) under general anesthesia was performed due to the malpresentation of the surviving twin.Discussion: The anesthetic strategy aimed to maintain maternal hemodynamic stability and prevent further bradycardia. Careful avoidance of bradycardia-inducing agents, such as opioids and certain inhalational agents, was critical. Close intraoperative monitoring was implemented, with a cardiology team on standby for immediate intervention if required. This case highlights the importance of multidisciplinary collaboration, hemodynamic optimization, and careful anesthetic planning in managing pregnant patients with CHB. The lack of established guidelines necessitates individualized management to ensure maternal and fetal safety.